Classroom assessment : - Airasian, Peter W. (McGraw-Hill, 2008)
Classroom Assessment: Concepts and Applications explores how assessment is a key component of all aspects of the instructional process, including organizing and creating a classroom culture, planning lessons, delivering instruction, and examining how students have grown as a result of instruction. The text also introduces pre-service teachers to new tools and approaches to classroom assessment that result from the infusion of computer-based technologies into schools.